Neuropeptide delivery to synapses by long-range vesicle circulation and sporadic capture. - Wong, M.Y.; Zhou, C.; Shakiryanova, D.; Lloyd, T.E.; Deitcher, D.L.; Levitan, E.S. (Cell, 2012)
Neurotransmission requires anterograde axonal transport of dense core vesicles (DCVs) containing neuropeptides and active zone components from the soma to nerve terminals. However, it is puzzling how one-way traffic could uniformly supply sequential release sites called en passant boutons. Here, Drosophila neuropeptide-containing DCVs are tracked in vivo for minutes with a new method called simultaneous photobleaching and imaging (SPAIM). Surprisingly, anterograde DCVs typically bypass proximal boutons to accumulate initially in the most distal bouton. Then, excess distal DCVs undergo dynactin-dependent retrograde transport back through proximal boutons into the axon. Just before re-entering the soma, DCVs again reverse for another round of anterograde axonal transport. While circulating over long distances, both anterograde and retrograde DCVs are captured sporadically in en passant boutons. Therefore, vesicle circulation, which includes long-range retrograde transport and inefficient bidirectional capture, overcomes the limitations of one-way anterograde transport to uniformly supply release sites with DCVs.